2021
DOI: 10.4070/kcj.2020.0391
|View full text |Cite
|
Sign up to set email alerts
|

An Open-label, Single-arm, Multicenter Feasibility Study Evaluating the Safety of Catheter-based Renal Denervation with DENEX™ in Patients with Uncontrolled Hypertension on Standard Medical Therapy

Abstract: Introduction: DENEX™ is a novel renal sympathetic denervation (RDN) system that is equipped with 3 electrodes that deliver radiofrequency energy to the renal nerves along renal arteries. The purpose of this study was to evaluate the safety and efficacy of RDN with DENEX™ in resistant hypertension. Methods: This was an open-label, single-arm, multicenter, first-in-man pilot study. Between March 2012 and August 2019, a total of 16 patients were enrolled at 4 centers in South Korea. The inclusion criteria were sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that the sympathetic nervous system is a special regulatory system between the kidney and the brain and plays an important role in the blood pressure regulation of hypertensive patients. Local norepinephrine isotope dilution was used to measure renal norepinephrine outflow in patients with untreated hypertension [16][17][18][19][20]. Monitoring revealed a high level of renal sympathetic outflow activation, indicating renal sympathetic hyperactivity, which is the core mechanism of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the sympathetic nervous system is a special regulatory system between the kidney and the brain and plays an important role in the blood pressure regulation of hypertensive patients. Local norepinephrine isotope dilution was used to measure renal norepinephrine outflow in patients with untreated hypertension [16][17][18][19][20]. Monitoring revealed a high level of renal sympathetic outflow activation, indicating renal sympathetic hyperactivity, which is the core mechanism of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Follow‐up duration ranged from 0.5 to 72 months. Ten studies reported data on plasma renin, 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 nine studies on plasma aldosterone, 14 , 15 , 16 , 18 , 19 , 21 , 22 , 23 , 24 two studies on plasma norepinephrine, 20 , 25 seven studies on serum sodium, 23 , 24 , 26 , 27 , 28 , 29 , 30 nine studies on serum potassium, 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 five studies on urinary sodium, 18 , 20 , 24 , 26 , 33 and two studies on urinary potassium. 24 , 26 The characteristics of included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…During this phase, a variety of new ablation catheters with different designs and energy sources were developed and subsequently evaluated in clinical studies with sham-controlled. At present, in addition to Medtronic SYMPLICITY Flex™ and Spyral™ catheters, other RDN catheters certified by European Union (excluding discontinued devices) include those using radiofrequency energy: Iberis (Terumo Corporation, Tokyo, Japan) [19] , DENEX™ (Handok Kalos Medical, Seoul, Korea) [20] , ConfidenHT™ System (Pythagoras Medical Ltd, Herzliya, Israel) [21] ; those utilizing ultrasound energy: Paradise (Paradise ultrasound system; ReCor Medical, Palo Alto, CA, USA) [18] and TIVUS™ (CardioSonic, Tel Aviv, Israel) [22] ; and those using anhydrous alcohol injection for ablation: Peregrine (Ablative Solutions Inc., Wakefield, MA, United States) [23] . These catheters represent a diverse range of technologies aimed at achieving RDN, providing clinicians with various options to tailor treatment according to individual patient needs and preferences.…”
Section: Rdn Treatment Technology Platformmentioning
confidence: 99%